Dari Kampus ke Negeri Sakura: Pemberdayaan Mahasiswa melalui Webinar Edukasi Ketenagakerjaan dan Budaya Kerja di Jepang - Frichicilia Grace Stahlumb; Bilqis Oktaviani Putri; Teddy Chrisprimanata Putra; Sarah Novianti; Ivandra Solihin (AJAD : Jurnal Pengabdian kepada Masyarakat, 2026)
Japan faces demographic challenges such as an aging population and a labor shortage, while Indonesia possesses a demographic bonus that has not yet been fully absorbed into the domestic labor market. These conditions create opportunities for employment cooperation between the two countries. However, students still encounter gaps in understanding regarding immigration regulations, academic preparedness, and cultural adaptation to Japan’s work environment. This activity, titled "Preparing Your Journey: Life of Foreign Worker in Japan", aims to equip students with knowledge of these aspects through an interactive webinar. Conducted online via Zoom, the activity follows the experiential learning cycle, including pre-test, content delivery by practitioners and experts, interactive Q&A, and post-test. Evaluation results show an increase in average scores from 78 to 90, confirming the effectiveness of this media as pre-departure education to support students’ informed decision-making for international careers.